2011
DOI: 10.5897/ajb10.1537
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation studies in Oryctes rhinoceros (L.) (Coleoptera: Scarabaeidae) from oil palm plantations using random amplified microsatellite (RAMs) markers

Abstract: Randomly amplified microsatellite markers were used to study the genetic variation among six populations of Oryctes rhinoceros L. which were collected from oil palm plantations in Selangor, Perak, Pahang and Medan. Samples were collected using light and pheromone trapping for the purpose of obtaining two populations per site study. Thirty individual beetles per population were screened using seven randomly amplified microsatellite primers. Beetles were not attracted to light traps at Pahang and Medan. This res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Based on the use of randomly amplified polymorphic DNA (RAPD) markers [50] and randomly amplified microsatellite markers (RAMs) [53], the possible presence of two separate gene pools in O. rhinoceros had been reported. However, when a morphometric analysis of O. rhinoceros was performed [54] it revealed that the beetles are morphologically indistinguishable; consequently strengthening the need for further molecular analysis of the insect.…”
Section: Control and Management Of Rhinoceros Beetles: Related Resear...mentioning
confidence: 99%
“…Based on the use of randomly amplified polymorphic DNA (RAPD) markers [50] and randomly amplified microsatellite markers (RAMs) [53], the possible presence of two separate gene pools in O. rhinoceros had been reported. However, when a morphometric analysis of O. rhinoceros was performed [54] it revealed that the beetles are morphologically indistinguishable; consequently strengthening the need for further molecular analysis of the insect.…”
Section: Control and Management Of Rhinoceros Beetles: Related Resear...mentioning
confidence: 99%